Commodification via the New Media: Content, Audience, and Labour in GoJek’s GoFood service - Adi, Kun Muhammad; Sujoko, Anang; Antoni, Antoni (LENTERA, 2021)
The existence of new media makes humans have control over the media they consume only through a smartphone on their hands. GoJek contributes new dynamics because the use of new media in the form of an application has changed most of the life patterns of media behavior. In the context of new media, media behavior is inseparable from the concept of political economy communication. This research uses a qualitative approach by extracting information from users, merchants, and drivers on GoFood service features taken by purposive sampling. The collected data from the result of observations, interviews, and documentation will be associated and analyzed using the political economy communication concept of Vincent Mosco, especially the commodification. Researchers found that the aspects of the commodification of content, commodification of audience, and commodification of labor of GoFood service features resulted in changes in society in adapting internet technology which also affected the welfare of the Indonesian economy.Keywords: GoFood, commodification, political economy of communication, and new media